Snowmobile impact on diurnal behaviour in the Arctic fox - Fuglei, Eva; Ehrich, Dorothee; Killengreen, Siw Turid; Rodnikova, Anna Y.; Sokolov, Aleksandr A.; Pedersen, Åshild Ønvik (Polar Research, 2017)
Source at http://dx.doi.org/10.1080/17518369.2017.1327300 As tourism increases globally, studies have documented impacts on wildlife from anthropogenic disturbances. In this observational experiment we aimed to investigate if snowmobile traffic affected the diurnal activity of Arctic fox in High Arctic Svalbard. We conducted the study in two areas in Svalbard, one control area with low snowmobile traffic and one experimental area with high snowmobile traffic. In each area 10 camera-traps, baited with reindeer carcasses, were positioned and programmed to take photographs every five minutes. The proportion of photographs with foxes was higher during the night than during the day, and the difference between night and day was larger in the area with more snowmobile traffic. By using data obtained according to a similar study design in two Arctic Russian sites, Yamal and Nenetsky, with little human activity and low snowmobile traffic, we were able to compare Arctic fox activity patterns in Svalbard on a larger scale. Our results indicate that snowmobile traffic had an impact on the diurnal activity of the Arctic fox in Svalbard, while there were no obvious diurnal activity patterns among Russian foxes. Even the area with low snowmobile traffic in Svalbard showed increased use of the reindeer carcasses during the night compared to one of the Russian sites, where foxes used carcasses equally during day and night. Such knowledge is of importance in designing cautious management practices.